The Male Virility vs. the Hegemonic Lady of the Bed: A Critical Study of the Iraqi Hanun Majeed’s Novel the Kingdom of the Happiest Home - Hussein, Ali Madhlum; Hashim, Alaa Abdulhussein; Mal-Allah, Abdul-Settar Abdul-Latif; Hamid, Hamid Hammood; Ibadi, Ahmed Hatim; Hasan, Zahraa Mohammed (Journal of Posthumanism, 2025)
This research tackles the Novel The Kingdom of the Happiest Home by the Iraqi novelist Hanun Majeed. It explores the implications of male virility and masculinity as a means to gain erotic pleasure and physical satisfaction versus the power of the female body. The research reveals what the novelist states in the introduction to his novel concerning the concept of Eros as being a duality of the lustful female and the sensuality of the virile male. Moreover, the research attempts to highlight the bearings of the lascivious corporeality and wantonness of the male as juxtaposed to the Iraqi realities and mishaps Iraqis suffered for a period covering the barren years of the Economic Blockade till the launch of the relentless 2003 war. The research shows how the novel excavates both rational and irrational dimensions rife in Iraqi society as far as Erotic satisfaction (for males and females) is concerned. This is because the novel unveils the body as a force and a will that transcends the ethical system in Iraq, which was corrupted by political power and its burdens on the economic will. The research stresses how the novel depicts how far the same corrupted ethics impose a state of exclusion and marginalization of the female. In addition, it ponders on the involved characters as cast in the novel: the characters which bear double meanings- they, on the one hand, are tethered to the past through memory, and on the other hand, they live and exist in the present through their kinetic actions and body movements. Also, the research makes it clear how the novel presents Iraq as a taut and frozen state that was falling, under the Economic Blockade and Sanctions, to the recesses of a fathomless abyss that has its own constraining obstacles and irrational effects, in all dimensions, on Iraqis’ kinetic actions and body movements; sexual practices, of course, are included. Hence, the research is divided into seven Sections and a Conclusion, ending with a list of the references used. The Sections are: 1. Introduction 2. Eroticism 3. The Novel The Kingdom of the Happiest Home 4. Aphorismatic Stimulation 5. Masculinity: An Epitome of Courage and Sexual Prowess 6. The Sacred and the Profane Dionysian 7. The Body as an Ontology of Strength.